Influence of co-ordination on butterfly propulsion index and velocity for butterfly expert swimmer - Boulesteix, L.; Chollet, D. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Introduction: The logic of the butterfly co-ordination for expert swimmers is associated with two undulations of legs for each complete arm cycle. Costill et al. (1992) and Maglischo (1993) showed that (1) the backward phase of the first undulation of legs was synchronised with the arm catch phase, and (2) the upward phase of the second undulation was synchronised with the arm pull phase. It seems nevertheless that this synchronisation depends on the increase of the velocity (Chollet & Boulesteix, 2001). The aim of this study was to evaluate the effects of the velocity increase on the arm and leg co-ordination but also to study this change of co-ordination through one tool of propulsion quantification during a swimming stroke. As Chollet et al. (2000) used the index of co-ordination to study the time gap between one arm and the other one based on injury times between the propulsive phases of every arm, we use the index of butterfly propulsion (IBP) to evaluate the time gap between the propulsive phases of the arms and legs for expert swimmers.